Handbook of entrepreneurship research : an interdisciplinary survey and introduction - Ács, Zoltán J.; Audretsch, David B. (International handbook series on entrepreneurship, 2010)
Introduction to the 2nd edition / Z. Acs, D. Audretsch -- Debates in entrepreneurship : opportunity formation and implications for the field of entrepreneurship / S. Alvarez, J. Barney, S. Young -- An update to the individual-opportunity nexus / J. Eckhardt, S. Shane -- Three views of entrepreneurial opportunity / S. Sarasvathy, N. Dew, S. Velamuri, S. Venkataraman -- Entrepreneurial behavior : firm organizing processes / W. Gartner, N. Carter, P. Reynolds -- Corporate entrepreneurship : an introduction and research review / D. Kuratko -- High-impact entrepreneurship / Z. Acs -- Equity financing / P. Gompers, J. Lerner -- Market processes and entrepreneurial studies / R. Koppl, M. Minniti -- Entrepreneurship, business culture and the theory of the firm / M. Casson -- Knowledge spillover entrepreneurship / Z. Acs, D. Audretsch -- Risk and uncertainty / S. Gifford -- Looking forward, looking backward : from entrepreneurial cognition to neuroentrepreneurship / N. Krueger, M. Day -- The social psychology of entrepreneurial behavior / K. Shaver -- Entrepreneurship as social construction : a multilevel evolutionary approach / H. Aldrich, M. Martinez -- International business, entrepreneurship and the global economy / S. Terjesen, Z. Acs, D. Audretsch -- The globalization of innovation and entrepreneurial talent / R. Wuebker, Z. Acs, R. Florida -- Entrepreneurship in developing countries / Z. Acs, N. Virgill -- The geography of entrepreneurship / L. Plummer, A. Pe'er -- The impact of entrepreneurship on economic growth / M. Carree, A. Thurik -- Entrepreneurship and public policy / M. Henrekson, M. Stenkula -- Connecting the study of entrepreneurship and theories of capitalist progress : an epilog / R. McGrath, S. Desai